2019
DOI: 10.4081/ejh.2019.3086
|View full text |Cite
|
Sign up to set email alerts
|

Alcian blue staining to track the intracellular fate of hyaluronic-acid-based nanoparticles at transmission electron microscopy

Abstract: The main step in the assessment of nanomaterial safety and suitability for biomedical use is the location and the dynamic tracking of nanoparticles (NPs) inside cells or tissues. To precisely investigate the uptake mechanisms and intracellular fate of NPs, transmission electron microscopy is the technique of choice; however, the detection of NPs may sometimes be problematic. In fact, while NPs containing strongly electron dense (e.g., metal) components do not require specific detection methods at the ultrastru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Previously, other stainings have been used for tracking nanoparticles, such as Alcian Blue in hyaluronic-acid-based nanoparticles in muscle cells to be visualized at transmission electron microscopy, 33 while our method appears to be the first used in plants for tracking lignin NCs with a fluorescent microscope in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, other stainings have been used for tracking nanoparticles, such as Alcian Blue in hyaluronic-acid-based nanoparticles in muscle cells to be visualized at transmission electron microscopy, 33 while our method appears to be the first used in plants for tracking lignin NCs with a fluorescent microscope in plants.…”
Section: Discussionmentioning
confidence: 99%
“…TEM images have also showed that several nanoconstructs are able to escape the endosomes and then occur freely in the cytosol, avoiding lysosomal degradation. This was first observed for cationic nanoconstructs and was explained by the so-called “proton sponge effect” [ 88 , 89 , 90 ] but recently, anionic nanocomplexes [ 91 ] and neutrally charged nanoparticles [ 92 ] have also been proven to efficiently escape endosomes. Endosomal escape has also been observed for gold nanoparticles coated with Listeriolysin O toxin, which is able to perforate the endosomal/lysosomal membrane [ 93 ] and, in prickly nanodiamonds, is able to break the endosome membrane [ 94 ].…”
Section: The Functional Value Of Ultrastructural Morphology In Nanomedical Investigationsmentioning
confidence: 99%
“…Alternative histochemical methods are, therefore, necessary to unequivocally reveal the nanoconstructs at an ultrastructural level. In a recent work, hyaluronic acid-based nanoparticles [ 163 ] were made recognizable in TEM by adapting the long-established Alcian blue staining [ 91 ] ( Figure 3 ) that was originally proposed to reveal glycosaminoglycans in tissue sections [ 164 ].…”
Section: Ultrastructural Histochemistry In Nanomedical Researchmentioning
confidence: 99%
“… 65 , 66 , 69 , 85 Recently, the Alcian blue staining has been used to detect hyaluronic-acid based NPs 86 at both bright-field microscopy and TEM. 87 Immunocytochemistry allowed detecting chitosan NPs loaded with a synthetic opioid at both FM and TEM, 88 and this technique may simultaneously be performed with photo-oxidation. 89 …”
Section: Imaging Techniques Applied To In Vitro Momentioning
confidence: 99%